Studies on seafood production systems in the South-west Region of Bangladesh - Islam, MR; Haque, MM; Rahman, MM (Journal of the Bangladesh Agricultural University, 2017)
The present study was conducted to understand existing production system of shrimp and prawn (seafood) with gher1 farming in the south-western region of Bangladesh from January to March 2014. Three gher farming clusters in three Upazilas of Bagerhat district were selected to carry out this study to assess the fact above using focus group discussion, key informant interview, questionnaire survey, physical observation, and literature review. The study revealed that gher farming system has changed the cropping patterns dramatically. This diversified farming system produces prawn, carp fish, boro paddy, and vegetable in the field where only single crop of paddy was cultivated. Gher dikes were used to produce vegetables, fruits and the central part for rice cultivation. Whereas the whole water body (during monsoon) and canals (during dry season) were used to culture finfish and prawn. Farmers were mainly found to use commercial feed with a rare amount of homemade feed because of the availability of commercial feed. Most of their investment goes for buying feed, PL and were found to take loan with high interest from banks or depot owners. Decreased salinity due to siltation in Mongla river resulted in increased overall production. The evidence presented in the study confirms that gher farming system impacting positively in the south-west region of Bangladesh. J. Bangladesh Agril. Univ. 15(1): 123-132, January 2017